The Role of the Yannas Husada Madura Pharmacy Academy Library in Enhancing Students' Reading Interest (A Case Study of Students at the Yannas Husada Madura Pharmacy Academy) - Tri Yanuar Putra (CV Media Inti Teknologi, 2026)
Background: Student reading interest remains relatively low despite the rapid growth of information availability in Indonesia. Academic libraries are recognized as strategic institutions in fostering literacy culture and supporting the learning process in higher education. Aims: This study aims to examine the role of the Yannas Husada Madura Pharmacy Academy Library in stimulating students' reading interest and to identify the steps required to cultivate a sustainable literacy culture among students. Methods: This study employed a qualitative descriptive approach with a case study design. Data were collected through observation, in-depth interviews with librarians, and documentation of library activities. Results: The findings reveal that the library has contributed significantly to enhancing students' reading interest through the provision of adequate collections, electronic services, information literacy programs, and reading promotion activities such as reading challenges and book review competitions. Nevertheless, several challenges persist, including limited reading space, insufficient digital literacy development, restricted access to literacy resources, suboptimal library location, and limited student accessibility. Conclusion: The library plays a meaningful role in promoting reading interest; however, continuous innovation in library services is essential to attract the attention of the modern digital generation and sustain a culture of reading among students.